Feasibility and Process Evaluation of a Need-Supportive Physical Activity Program in Aged Care Workers: The Activity for Well-Being Project - Lock, Merilyn; Post, Dannielle; Dollman, James; Parfitt, Gaynor (Frontiers in Psychology, 2020)
The need to undertake pilot-testing and evaluation of novel health promotion programs has become increasingly apparent for the purpose of understanding the true effects of complex interventions, and for testing and refining behavioural theories that these interventions are informed by. A mixed methods process evaluation and feasibility study was undertaken for a need-supportive physical activity program that was piloted in a single-group pre-post study. The piloted program was designed to support participant needs of autonomy, competence and relatedness through evidence-based and theory-informed behaviour change strategies including a Motivational Interviewing style appointment, education on self-management tools (i.e. pedometers, goal-setting, action and coping planning, and a customised website for goal-setting and self-monitoring), and Self-Determined modes of regulating physical activity intensity (affect, RPE and self-pacing). The program aimed to positively impact physical activity behavior, psychological wellbeing and associated motivational processes. Reach, adoption, fidelity, context, change and performance objectives, and feasibility of the program were evaluated using information from survey respondents from the target population (n = 118) and implementing staff (n = 6), questionnaires from pilot study participants (n = 21) and individual semi-structured, interviews with pilot study participants, non-participants, and implementing staff (n = 19). Process evaluation of the Activity for Wellbeing Program found that the reach of the program was moderate but adoption was low. The use of self-management tools and Self-Determined modes of regulating physical activity intensity appeared to be feasible. The website had mixed responses and low engagement. The element of having a support person elicited a strong positive response in the program participant interviews. Involving local implementing staff more directly into the delivery of the intervention could have potentially improved reach, adoption and feasibility of the program.